Genome sequence of thermophilic cellulolytic actinobacterium Thermobifida fusca strain UPMC 901 producing thermostable cellulases. - Zainudin, Mohd Huzairi Mohd; Gan, Han Ming; Tokura, Mitsunori (Elsevier, 2024)
Thermophilic cellulolytic bacteria producing thermostable cellulase have multiple potential industrial and biotechnological applications. In this study, we sequenced the genome of Thermobifida fusca UPMC 901 by using nanopore sequencing technology with 100 % genome coverage. The represented genome is 3.76 Mb with a G + C content of 67.4 %. The genome is composed of 1 scaffold with 3207 protein-coding genes. The results indicated that the genome of the Thermobifida fusca gene encodes at least 112 genes for carbohydrate-active enzymes. Of these genes, 40 glycoside hydrolases (GHs), 36 glycosyl transferases (GTs), 22 carbohydrate-binding modules (CBMs), 9 carbohydrate esterases (CEs), 3 polysaccharide lyases (PL) and 2 auxiliary activity (AAs) which refer to as lytic polysaccharide monooxygenase (LPMO), gene encoding the copper-dependent enzymes that catalyse oxidative cleavage of recalcitrant crystalline cellulose, were identified. In addition, two new functional genes, amylo-α-1,6 glucosidase and endo-α-1,4-mannosidase were also detected in the T. fusca genome. This study represented the ninth genome of the T. fusca and the cellulase genes identified will facilitate the exploration of potential sources for industrial and agricultural applications.